Community Empowerment of Persons with Disabilities through Creative Batik Ciprat Training in Karangpatihan Village, Ponorogo Regency - Mulyadi, Eko; Riyanto, Yatim; Mardliyah, Sjafiatul (IKIP Widya Darma Surabaya, 2025)
Objective: This study aims to examine the empowerment process of individuals with mild intellectual disabilities through a community-based batik ciprat training program in Karangpatihan Village, Ponorogo Regency. The research focuses on three main Aspects include the empowerment process, supporting factors, and inhibiting factors in the program's implementation. Method: A qualitative approach with a phenomenological method was employed. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using thematic analysis techniques. Results: The findings reveal that the batik ciprat training, conducted through a collaborative approach, effectively enhances the participants' self-confidence, creativity, and economic independence. The success of the program is strongly supported by multi-stakeholder synergy, particularly the active roles of Rumah Harapan Mulya Social Welfare Institution (LKS), village government, local volunteers, and higher education institutions. Beyond technical skill training, the program also Serves as a platform for social integration of people with disabilities. Challenges encountered include communication barriers, varying levels of participant ability, and technical constraints such as limited production facilities and market access. Nevertheless, the adaptive and community-based approach has proven capable of Addressing most of these challenges. Novelty: The program demonstrates that the empowerment of vulnerable groups can succeed when implemented collaboratively and contextually.